2004
DOI: 10.1111/j.1439-0264.2004.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of Lingual Papillae in the Common Shrew, Sorex araneus, L.

Abstract: The dorsal surface of the tongue of the adult common shrew (Sorex araneus L.) was examined by scanning electron microscopy. As in the other insectivores, three types of lingual papillae were observed: filiform, fungiform and vallate papillae. The filiform papillae represented the most numerous type of lingual papillae. The characteristic feature of the filiform papillae, covering the apex and corpus of the tongue, is the two processes tilted to the root of the tongue. The filiform papillae on the lingual apex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Th e fungiform papillae in guinea pig (Kobayashi, 1990), goat (Kurtul, Atalgin, 2008), Persian squirrel (Goodarzi, 2014) and maned sloth (Benetti et al, 2009) are reported to be concentrated on the lingual apex and also on both lateral borders. However, fungiform papillae in the common shrew are restricted to the lingual corpus (Jackowiak et al, 2004). Nasr (2012) reported that fungiform papillae of Erinaceous auritus are populated on the apex of the tongue and form clusters of two or three papillae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e fungiform papillae in guinea pig (Kobayashi, 1990), goat (Kurtul, Atalgin, 2008), Persian squirrel (Goodarzi, 2014) and maned sloth (Benetti et al, 2009) are reported to be concentrated on the lingual apex and also on both lateral borders. However, fungiform papillae in the common shrew are restricted to the lingual corpus (Jackowiak et al, 2004). Nasr (2012) reported that fungiform papillae of Erinaceous auritus are populated on the apex of the tongue and form clusters of two or three papillae.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in various mammalian species indicate that there is a wide variability in morphological features of lingual papillae and a close correlation between lingual papillae structure, feeding habits and taxonomy (Jackowiak, Godinicki, 2005). Although, this variability is remarkable between high systemic units, such as orders and families, interspecies diff erences are also seen frequently (Iwasaki, 2002;Kobayashi et al, 2005;Emura et al, 2006;Jackowiak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Insectivore tongues possess one paired vallate papillae, e.g. in tree shrew (Kobayashi & Wanichanon, 1992), European mole (Jackowiak, 2006) and common shrew (Jackowiak et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated morphological diversity among the oral tissues of mammals (Nickel et al., ), particularly with respect to the three‐dimensional structure of the papillae linguales and their connective tissue cores (CTCs) in terrestrial species (Kobayashi et al., , ; Kobayashi, ; Adnyane et al., ; Watanabe et al., ). Following the early macroscopic studies of insectivores by Sonntag (), there have been several detailed morphological investigations into the papillae linguales of the Soricomorpha, for example, Talpidae such as Mogera (Kobayashi et al., ; Miyata et al., ), Talpa (Jackowiak, ) and Dymecodon (Kobayashi et al., ); and Soricidae including Solex , (Kobayashi and Iwasaki, ; Jackowiak et al., ), Suncus (Kobayashi et al., ; Kobayashi and Iwasaki, ), Chimarrogale (Kobayashi and Iwasaki, ) and Crocidura (Kobayashi (), Kobayashi et al. (, ).…”
Section: Introductionmentioning
confidence: 99%